Chemical Castration Sanctions in an Ethical Perspective - Yovita Arie Mangesti (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2022)
Chemical castration is an additional sanction imposed on perpetrators of sexual violence against children. This sanction was imposed as an implementation of the child protection law. This additional sanction is threatened with the consideration that every act of sexual violence leaves a psychological trauma for the child that affects the child's growth and development in his life. This study is normative legal research with a statutory approach, a conceptual approach, and a philosophical approach to analyse the Child Protection Act and the PP Chemical Castration. A philosophical approach is used to examine ethical and legal aspects as the implementation of the protection of human dignity. The results of the research from the ethical perspective concluded that the imposition of chemical castration sanctions is unethical (unethical), this is a paradox with the aim of restorative justice theory as a new vision in criminal law enforcement. With a legal, conceptual, and scholastic approach to the Implementation Regulations for Chemical Castration with ethical perspective parameters, the imposition of additional sanctions is unethical and in line with restorative justice that prioritizes human values ??for perpetrators, victims, and implementers of chemical castration. The imposition of sanctions must pay attention to the principle of respect for human values ??as a whole person (respect for person) and the principle of access to justice (justice for all).